Efficacy and Safety of Fluconazole Mucoadhesive Patches in Human Immunodeficiency Virus-Related Oral Candidiasis - Srikanth Deenadayalan MD; Ashok Shenoy MD; Ashwin Kamath MD; Mahalaxmi Rathnanand PhD; Sheetal Ullal MD; Nandita Shenoy MDS (Journal of the International Association of Providers of AIDS Care)
Background Opportunistic fungal infections like oral candidiasis account for a significant amount of morbidity in HIV disease and an indicator of immune suppression. Fluconazole is a broad-spectrum antifungal agent that has been extensively used in the management of oral, candidiasis. Highly efficacious fluconazole is also known to have systemic toxicity due to high drug interaction and hence the present study focuses on the formulation of bioadhesive film as a controlled release carrier for fluconazole. Materials and Methods Patients were randomised, using a computer-generated list of random numbers, into one of the three groups: patients in group A received fluconazole mucoadhesive film 20 mg (sustained release) that was to be applied at bedtime and film 10 mg (intermediate release) to be applied during the day after lunch. Results There was a significant decrease in oral discomfort, pain and clinical improvement in group A compared to group B (Fluconazole oral tablets 100 mg/day) (P = 0.005) and group C (Fluconazole Mouth rinse) (P = 0.002). The patients who received the mucoadhesive patches had a more tolerable safety profile as expected compared to the other groups. Conclusion The bioadhesive films of fluconazole were used in HIV positive patients with oral candidiasis to overcome the problems of high dose requirement of the drug and reduce associated adverse reactions in an already immunocompromised patients and improve the quality of life.